A Person-Centred Approach When Encountering Students With Recurrent Pain: School Nurses' Experiences. (August 2021) - Wigert, Helena; Fors, Andreas; Nilsson, Stefan; Dalenius, Kristina; Golsäter, Marie
Stress has a negative impact on students' daily lives and can be associated with recurrent pain. School nurses play a key role in supporting young people with stress-related pain. The purpose of this qualitative interview study was to elucidate school nurses' experiences of encountering students with recurrent pain when practicing person-centred care. The school nurses were based at public and private schools and worked with students aged 12-19. Data were collected through interviews with 18 school nurses and analyzed with deductive content analysis. The school nurses felt that actively listening to the students' narratives about daily life with recurrent pain, and co-creation of a health plan, encouraged the students to participate as partners in their own care and strengthened their relation with the students. The application of a person-centred approach in school health care meant that traditional knowledge transfer was replaced with a dialogue that reflects both the student's and school nurse's perspective.